The Relationship Between Different Levels of Income to Stock Price of Manufacturing Companies in Indonesia - Lule, Benny (JBE (Journal of Business and Economics); Volume 10 No.1, 2011 JBE UNKLAB, 2011)
This Study is to Analyze the Relationship between different levels of income with stock price for five segments of manufacturing companies. The study divides different level of income into three parts namely, Gross Profit, Earnings Before Interest and Tax, and Net Income, Spearmen rank correlation was used to test the relationship between different levels of income with stock price. The findings indicate that Gross Profit is related to Stock Price but not for EBIT and Net Income.